Increasing self-esteem of high school students through narrative counseling - Hilman, Najma Sana Nadhirah; Hafina, Anne; Ilfiandra, Ilfiandra (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This research aims to show that narrative counseling can increase adolescents' self-esteem. The research approach used is mixed-method with an embedded design. The instrument is based on the Coopersmith Self-Esteem Inventory (CSEI) which measures four aspects of self-esteem. The research subjects in this study were 3 high school adolescents in class XI. The results of the research showed that there was a change in self-esteem in the three teenagers, which was indicated by receiving sufficient recognition and feeling worthy, which means that narrative counseling can increase the self-esteem of adolescents who experience self-harm. However, of the three adolescents, one adolescent still committed self-harm with infrequent frequency even though his self-esteem was already in the medium category. This suggests that there are other variables that influence someone to do self-harm, such as self-concept. Apart from that, the factors influencing a person's self-esteem are different. Further analysis is needed regarding these factors.